Analisis Pengaruh Pemberian Insentif (Incentive) dan Pelatihan Kerja Terhadap Motivasi dan Kinerja Karyawan Kantor Bahasa Provinsi Lampung - Muhammad Arief Arfandi; Ade Candra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of incentives and job training on the motivation and performance of employees at the Language Office of Lampung Province. Incentives and job training are crucial factors in enhancing employee motivation and performance within organizational settings. The research employed a quantitative approach, utilizing survey data from employees of the Language Office. Statistical analysis techniques such as regression analysis were applied to examine the relationships between incentives, job training, employee motivation, and performance.the findings suggest that both incentives and job training significantly impact employee motivation and subsequently influence their performance levels. Recommendations based on the study advocate forthe enhancement of incentive systems and the implementation of effective job training programs to foster higher motivation and better performance among employees in the Language Office of Lampung Province. Future research could explore additional variables or conduct longitudinal studies to further understand the dynamics ofemployee motivation and performance in similar organizational contexts.